2021
DOI: 10.1029/2021gl096579
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Correlation Between Evapotranspiration and Gravity at a Daily Time Scale From Two Vertically Spaced Superconducting Gravimeters

Abstract: Evapotranspiration (ET) is a key variable to understanding eco-hydrosystems because it links water, carbon, and energy cycles (Fisher, 2014). ET is a major component of the water cycle, accounting for approximately 70% of precipitated water at the continental scale (Fisher et al., 2017;Oki & Kanae, 2006). Several approaches exist for estimating ET, but large uncertainties persist and estimates remain difficult to validate, particularly at large scale (Müller & Bolte, 2009;Verstraeten et al., 2008). New approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…They interpreted the daily change in the gravity signal as water loss through evapotranspiration. Carrière et al (2021a) showed a day-to-day correlation between the daily variation of gravity and the modelled ET of a Mediterranean holm oak (Quercus ilex L.) forest. In their study, the authors subtract the signal of two superconducting gravimeters superimposed onto each other with a 500 m altitude difference to achieve the accuracy needed to interpret the evapotranspiration signal.…”
Section: Figure 3: (A) Cross-sectional View Of the Sp Sensor Array Re...mentioning
confidence: 92%
“…They interpreted the daily change in the gravity signal as water loss through evapotranspiration. Carrière et al (2021a) showed a day-to-day correlation between the daily variation of gravity and the modelled ET of a Mediterranean holm oak (Quercus ilex L.) forest. In their study, the authors subtract the signal of two superconducting gravimeters superimposed onto each other with a 500 m altitude difference to achieve the accuracy needed to interpret the evapotranspiration signal.…”
Section: Figure 3: (A) Cross-sectional View Of the Sp Sensor Array Re...mentioning
confidence: 92%
“…Due to these characteristics, SGs have been used as hydrological sensors for calibration and validation of hydrological models [24], for monitoring the artificial recharge of an aquifer [25], and for estimating specific yields [26]. In addition, SG data can be used to estimate ET at the mesoscale [8,[27][28][29][30]. Van Camp et al [27] applied a stacking process to gravity time series for rain-free periods to isolate the effect of ET on the gravimetric signal and thus estimate the daily mean ET rate.…”
Section: Introductionmentioning
confidence: 99%
“…These ET estimates were then validated with data recorded by a lysimeter. Carrière et al [28] estimated daily ET in a rain-free period using data from two superconducting gravimeters vertically separated by a distance of 512 m. This arrangement between the gravimeters eliminates the non-hydrological large-scale effects observed by both instruments, improving the analysis of local water storage changes.…”
Section: Introductionmentioning
confidence: 99%